2017
DOI: 10.1155/2017/8494572
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Products Potently Modulate Experimental Autoimmune Encephalomyelitis by Downregulating Neuroinflammation and Promoting a Suppressive Microenvironment

Abstract: A negative correlation between the geographical distribution of autoimmune diseases and helminth infections has been largely associated in the last few years with a possible role for such type of parasites in the regulation of inflammatory diseases, suggesting new pathways for drug development. However, few helminth-derived immunomodulators have been tested in experimental autoimmune encephalomyelitis (EAE), an animal model of the human disease multiple sclerosis (MS). The immunomodulatory activities of Taenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
(73 reference statements)
0
27
0
Order By: Relevance
“…IL-33 enhances both Th2 effector responses and activation of Treg by Type-2 cytokines ( 73 , 74 ), thus these findings may complement those described here. Other immune regulatory mechanisms may be induced by type-2 responses, including alternate activated macrophages (M2), which are induced when parasite infection reduces severity of EAE ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 enhances both Th2 effector responses and activation of Treg by Type-2 cytokines ( 73 , 74 ), thus these findings may complement those described here. Other immune regulatory mechanisms may be induced by type-2 responses, including alternate activated macrophages (M2), which are induced when parasite infection reduces severity of EAE ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous recovery from EAE is associated with activation of Treg that promote recovery ( 29 , 30 ). Parasitic infections reduce severity of EAE, including Th17 response and T cell infiltration to central nervous system (CNS) ( 31 , 32 ). Parasitic infections that reduce severity of EAE and induce Treg include Trypanosoma cruzi ( 33 ), Plasmodium chaubaudi ( 34 ), Trichinella spiralis ( 35 ), and Nippostrongylus brasiliensis ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current study we found HES was only able to delay disease onset indicating that the immunological changes produced by HES were not strong enough to recapitulate the effect seen with live parasite infection. In contrast, a study with Taenia crassiceps ES (TcES), which showed that in addition to Th2-deviation, ES was able to sequester inflammatory cells into the periphery and therefore inhibit the induction of EAE by preventing trafficking of cells to the CNS ( 43 ), a mechanism that could well underpin the protective ability of live H. polygyrus . Soluble egg antigens (SEA) from S. japonicum and T. spiralis ES also ameliorate EAE disease in a way that was similar to whole parasite infection, protection that was related to a Th2 shift in both the periphery and CNS ( 19 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SADBE treatment can be replaced by the transfer of MDSC ( 262 ). In EAE, it was demonstrated that helminth products stimulate the production of TH2 cytokines and suppress TH1 and TH17 responses, the therapeutic efficacy exceeding that of corticosteroid treatment ( 263 ). Another option are statins, which are cholesterol lowering drugs, also described to induce immunosuppression.…”
Section: Recruiting Mdsc and Mdsc-exo In Autoimmune Diseasementioning
confidence: 99%